2016
DOI: 10.1111/1744-7917.12371
|View full text |Cite
|
Sign up to set email alerts
|

Population structuring of the ubiquitous stingless bee Tetragonisca angustula in southern Brazil as revealed by microsatellite and mitochondrial markers

Abstract: Tetragonisca angustula is one of the most widespread stingless bees in the Neotropics. This species swarms frequently and is extremely successful in urban environments. In addition, it is one of the most popular stingless bee species for beekeeping in Latin America, so nest transportation and trading is common. Nest transportation can change the genetic structure of the host population, reducing inbreeding and increasing homogenization. Here, we evaluate the genetic structure of 17 geographic populations of T.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 81 publications
2
12
0
Order By: Relevance
“…Although we cannot discard sampling errors, the presence of several exclusive haplotypes in each collecting site is also an indication of very low current female migration and suggests that females may exhibit philopatry (Rowe et al 2017). This same scenario and biological interpretation have been commonly reported for several eusocial bee species (Yanega 1990;Francisco and Arias 2009;Brito and Arias 2010;Bonatti et al 2014;Francisco et al 2016b). Primitively eusocial and solitary bees are generally not philopatric (Kim et al 2008;Francisco et al 2016a;Rosa et al 2016;Luna-Lucena et al 2017;Toledo et al 2017), but some exceptions have been reported (Ferreira et al 2013;López-Uribe et al 2014Penha et al 2015).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although we cannot discard sampling errors, the presence of several exclusive haplotypes in each collecting site is also an indication of very low current female migration and suggests that females may exhibit philopatry (Rowe et al 2017). This same scenario and biological interpretation have been commonly reported for several eusocial bee species (Yanega 1990;Francisco and Arias 2009;Brito and Arias 2010;Bonatti et al 2014;Francisco et al 2016b). Primitively eusocial and solitary bees are generally not philopatric (Kim et al 2008;Francisco et al 2016a;Rosa et al 2016;Luna-Lucena et al 2017;Toledo et al 2017), but some exceptions have been reported (Ferreira et al 2013;López-Uribe et al 2014Penha et al 2015).…”
Section: Discussionsupporting
confidence: 76%
“…Genetic analysis has been well stated as an efficient approach to answer questions of ecology and genetics. In attempts to understand population dynamics, genetic diversity, relatedness, sex dispersal pattern, species richness, and measure of the anthropogenic impacts, studies using molecular markers allied to population genetic analysis tools have already been conducted on bees (Freitas et al 2009;Carvalho and Del Lama 2015;dos Santos et al 2016a, b;Francisco et al 2016b;Frantine-Silva et al 2017;López-Uribe et al 2017;Lozier and Zayed 2017;Chapman et al 2018;Françoso et al 2018). We performed genetic analysis using mitochondrial and nuclear molecular markers in order to resolve some of the basic questions concerning T. diversipes general biology.…”
Section: Introductionmentioning
confidence: 99%
“…Although they have a limited dispersal capability in comparison to A. mellifera (Ruttner and Ruttner 1972;Baudry et al 1998), a lack or low genetic structure for nearby natural populations of T. angustula has been attributed to the males (Francisco et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the mode of reproduction, stingless bees have strong dispersal limitations (Rasmussen and Cameron 2010), and are therefore of particular interest for the study of relationships between islands and continents (Roubik and Camargo 2012). The study of bee populations located on islands is also of interest to understand aspects related to extinction risks, possible bottleneck effects, gene drift, and inbreeding in haplodiploid Hymenoptera (Alves et al 2011;Francisco et al 2016Francisco et al , 2017Soro et al 2017).…”
Section: Introductionmentioning
confidence: 99%